Restoring stone monuments: Enlightening critical details by the combined use of innovative sensing techniques (Fracture and Structural Integrity, 2019)
The experience gathered during the implementation of long series of laboratory experimental protocols, aiming to study the mechanical response of restored structural elements, is summarized. Conclusions are drawn concerning the proper exploitation of the laboratory results in field applications in the frame of on-going restoration projects of ancient stone monuments. The need of continuous bidirectional interaction between the scientific personnel working in the site and the scientists working in the laboratory is emphasized. The role of the Digital Image Correlation technique in quantifying parasitic effects influencing the laboratory data is proven decisive. The need to use modern sensing techniques, providing data from the interior of loaded restored complexes (simulating restored structural elements), like the Pressure Stimulated Currents and the Acoustic Emissions ones, according to a combined manner is highlighted. The capability of these two techniques to monitor the damage evolution within the mass of the elements tested and to provide clear pre-failure indicators renders them flexible tools in the hands of engineers designing the restoration projects.
Keywords: 3D digital image correlation; Acoustic emissions; Pressure stimulated currents; Dionysos marble; Monuments